Spectroscopic analysis of bosentan in biological samples after a liquid-liquid microextraction - Sanaz Sajedi-Amin; Karim Assadpour-Zeynali; Vahid Panahi-Azar; Abbas Kebriaeezadeh; Maryam Khoubnasabjafari; Khlalil Ansarin; Vahid Jouyban-Gharamaleki; Abolghasem Jouyban (BioImpacts, 2015)
Introduction: Microextraction processes with UV-Vis measurement have been developed and validated for analysis of bosentan in biological samples. Methods: In this work, liquid–liquid microextraction procedures (DLLME & USAEME) were employed for cleanup, pre-concentration, and determination of bosentan in biological samples by UV-Vis spectroscopy at 270 nm. The method was validated and applied to the determination of bosentan in spiked serum, exhaled breath condensate and urine samples. Results: Various experimental factors including type of extraction and dispersive solvents and their volumes, pH, sonication time and centrifuging time were investigated. Under the optimum conditions, the method was linear in the range of 1.0–5.0 μg.mL−1, with coefficient of determination (R2) of > 0.998. The limit of detection (LOD) was 0.07 mg.L−1. Recovery of the target analyte in biological samples was 106.2%. The method could be easily applied for higher concentration of bosentan and needs more improvement for application in the pharmacokinetic investigations where more sensitive methods are required. Conclusion: A simple, low cost, precise and accurate spectrophotometric analysis of bosentan in biological samples after liquid-liquid microextraction were developed and validated for routine analyses.